Health economic evaluations of visceral leishmaniasis treatments: a systematic review. - Daniel S Marinho; Carmen N P R Casas; Claudia C de A Pereira; Iuri C Leite (PLoS Neglected Tropical Diseases)
Objective The main objective of this study was to identify, describe, classify and analyze the scientific health economic evidence of VL-related technologies. Methods A web search of combinations of free text and Mesh terms related to the economic evaluation of visceral leishmaniasis was conducted on scientific publication databases (Web of Science, Scopus, Medline via the Pubmed and Lilacs). A manual search of references lists of articles previously identified by the authors was also included. Articles written in English, Portuguese, Spanish or French were considered suitable for inclusion. Articles that matched the inclusion criteria were screened by at least two researchers, who extracted information regarding the epidemiologic scenario and methodological issues on a standardized form. Results The initial search retrieved 107 articles, whose abstracts were inspected according to the inclusion criteria leading to a first selection of 49 (46%) articles. After the elimination of duplicates, the list was reduced to 21 (20%) articles. After careful reading and application of exclusion criteria, 14 papers were eligible according to the description, classification and analysis process proposed by the study. When classified by type of economic evaluation, articles were 7 (50%) cost-effectiveness, 5 (36%) cost-minimization, 1(7%) cost-benefit, and 1(7%) budget impact. When classified by methodology, studies were mainly nested to clinical-trials ("piggy back") 8(57%). Discount rates for outcomes and costs were present in 3 (43%) of the cost-effectiveness studies, and according to WHO's recommendations, the discount rate of 3% was used in all studies. Conclusions This article showed that health economic evaluations on visceral leishmaniasis used a wide range of technologies and methods. Nevertheless it is important to point out the geographic concentration of studies, which makes their transferability uncertain to different epidemiological scenarios, especially those concerning visceral leishmaniasis caused by Leishmania infantum.